A systematic review of interventions targeting men's alcohol use and family relationships in low- and middle-income countries. (7th March 2018) - Giusto, Ali; Puffer, Eve
Abstract : Background: Problem drinking accounts for 9.6% of disability-adjusted life years worldwide. It disproportionally affects men and has disabling physical, psychological, and behavioral consequences. These can lead to a cascade of negative effects on men's families, with documented ties to intimate partner violence (IPV) and child maltreatment. These multi-level problems are often exacerbated where poverty rates are high, including low and middle-income countries (LMICs). In contexts where strong patriarchal norms place men in positions of power, family-level consequences are often even more pronounced. Methods: We conducted a systematic review of the literature on interventions in LMICs targeting men's problem drinking and any family-related outcomes. Cochrane and PRISMA procedures guided the review. The search was conducted in PsychInfo, PubMed, and Web of Science. Results: The search yielded 1357 publications. Nine studies from four different countries met inclusion criteria. Of those, only one had the primary goal of simultaneously improving drinking and a related family-level outcome (IPV). Six of the studies documented modest improvements on both drinking and couples or family outcomes. Strategies common to these included cognitive-behavioral techniques, communication skills training, narrative therapy, and participatory learning. Gender-transformative approaches were associated with reduced IPV and more equitable gender norms, and motivational interviewing and behavioral approaches were beneficial for reducing alcohol use. Conclusions: Findings highlight the scarcity of interventions addressing men's drinking and its effects on families, particularly for parent-child outcomes. However, results point to strategies that, combined with other evidence-based family interventions can guide the development and rigorous evaluation of integrated programs.